The ethics of marketing in Muslim and Christian communities: Insights for global marketing - Gibbs, Paul; İlkan, Mustafa; Pouloukas, Stavros (Equal Opportunities International, Emerald Group Publishing, 2007)
Purpose – This paper takes advantage of the closeness of two secular, separated communities on the island of Cyprus to study how controversial products and forms of offensive advertising can be related to levels of religiousness, time usage and temporality. The resulting observations are then offered as insights into the notion of ethics in the two religious groups and how these might influence marketing to multicultural communities. Design/methodology/approach – The findings are based on a small-scale survey of 530 students (211 Christians, 302 Muslims and 18 undeclared) who responded to a questionnaire distributed at two privately owned, English speaking institutions, one in the north and one in the south part of Cyprus. Findings – This study indicates a high degree of commonality between Muslim and Christian students living in the adjoining communities in Cyprus. In general, overall reactions were tolerant of most products and forms of advertising, but where there were differences occurred there were specific reactions to the forms of the advertising. Significant differences were found across the communities when devoutness was tested especially regarding products that were of a sexual nature. Research limitations/implications – The relatively small numbers studied in the special case of Cyprus and the focus on students could limit the generalisation of these results. Practical implications – The results raise some issues for marketing segmentation and image use. For instance, positive and forward-looking images would stimulate most of the group regardless of their level of faith. Originality/value – This paper identifies commonalties and also ontological differences that could have implications for global marketing campaigns.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1108/02610150710822311) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Cyprus; Advertising; Target audience; Islam; Christianity; Ethics